2014
DOI: 10.4308/hjb.21.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Physicochemical Properties of Indonesian Indica Rice Using Molecular Markers

Abstract: Physicochemical properties determine the palatability and cooking quality of rice, which must be determined efficiently in order to satisfy consumer demand. To date, little information exists on the use of molecular markers to predict physicochemical properties of the "indica" rice varieties found in Indonesia. The objective of this study was to investigate physicochemical properties and genetic variation of Indonesian rice varieties, and to formulate regression equations to analyze sets of DNA markers which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…Protein content in this study varied from 6.51 to 9.13% and was comparable to that found by Thomas et al [17] and Lestari et al [29]. The protein content values of Asaduzzaman et al [30] and Rohman et al [31] were found less or near to the results of this study.…”
Section: Discussionsupporting
confidence: 84%
“…Protein content in this study varied from 6.51 to 9.13% and was comparable to that found by Thomas et al [17] and Lestari et al [29]. The protein content values of Asaduzzaman et al [30] and Rohman et al [31] were found less or near to the results of this study.…”
Section: Discussionsupporting
confidence: 84%
“…Penggunaan lebih banyak marka molekuler yang polimorfis juga perlu dilakukan untuk memperoleh hasil pengelompokan aksesi yang lebih baik. Hal ini tidak hanya akan meningkatkan akurasi studi diversitas genetik, tetapi juga dapat menjadi dasar pengembangan set marka molekuler berbasis formula regresi dan analisis komponen utama untuk memprediksi karakter palatabilitas beras (Lestari et al 2009;Lestari et al 2014).…”
Section: Analisis Klaster Aksesi Padi Warna Lokal Indonesiaunclassified
“…Secara umum Kalimutu memiliki rataan kesamaan genetik paling rendah dengan varietas lain. Variasi yang luas yang terlihat pada varietas indica dapat disebabkan oleh bervariasinya ekosistem penanaman di Indonesia misalnya di lahan sawah, tadah hujan dan rawa (Lestari et al, 2014). Secara keseluruhan antara varietas japonica dan indica, koefisien kesamaan yang paling rendah (0,4) dalam arti jarak genetik paling jauh ditemukan antara varietas japonica dan indica baik varietas elit maupun lokal, khususnya Onnuri atau Manmi dengan Cigeulis atau Fatmawati.…”
Section: Sbe2unclassified